The Influence of Beauty Vloggers and E-WOM on the Decision of Young Women in Pontianak City to Purchase Local Cosmetic Products through Customer Trust - Venny Angelia; Graceallah, Georgerius (Economos : Jurnal Ekonomi dan Bisnis, 2025)
This study analyzes the influence of beauty vloggers and E-WOM on the purchase decision of local cosmetic products through customer trust among teenage girls in Pontianak City. The main problem is teenage girls' doubts about the quality of local cosmetic products and their lack of trust in information from beauty vloggers and E-WOM. The study period was taken from Juni to September 2025. Using a quantitative causal associative approach with a Likert scale questionnaire survey of 161 respondents through strata quota sampling and purposive sampling techniques. The data were analyzed using SEM-AMOS. The results show that beauty vloggers and E-WOM have a significant positive effect on customer trust, but not directly on purchasing decisions. Customer trust has a significant positive effect on purchasing decisions. The Sobel Test proves that customer trust mediates the influence of beauty vloggers and E-WOM on purchasing decisions. The study shows the importance of building consumer trust as a bridge between digital influence and actual purchasing decisions.